The effect of physical activity on fertility: a mini-review - Minhal Mussawar, B.Sc; Ashley A. Balsom, M.A; Julia O. Totosy de Zepetnek, Ph.D; Jennifer L. Gordon, Ph.D (Elsevier, 2023)
Although lifestyle factors such as diet, cigarette smoking, and alcohol consumption are increasingly recognized as important contributors to the risk of subfertility, the role of exercise in fertility remains less clear. As such, it is challenging for healthcare providers to deliver clear, evidence-based recommendations to patients regarding the optimal frequency and intensity with which they should exercise to maximize their chances of conception. Therefore, this review provides a critical overview of the available research for various patient populations.